2019
DOI: 10.1103/physrevresearch.1.033163
|View full text |Cite
|
Sign up to set email alerts
|

Waiting time distributions in a two-level fluctuator coupled to a superconducting charge detector

Abstract: We analyze charge fluctuations in a parasitic state strongly coupled to a superconducting Josephson-junction-based charge detector. The charge dynamics of the state resembles that of electron transport in a quantum dot with two charge states, and hence we refer to it as a two-level fluctuator. By constructing the distribution of waiting times from the measured detector signal and comparing it with a waiting time theory, we extract the electron in-and out-tunneling rates for the two-level fluctuator, which are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…(ii) The estimated best-fit Δ P ± parameters correlate well with the standard deviation of the P ± in the underlying simulation. (iii) Even a single fluctuator with a fixed switching rate (bimodal distribution of P ± and a Poisson distribution of switching times 40 ) can generate detectable excess noise still consistent with our Dirichlet-based statistical models. As for the physics of the real device in a noisy environment, the simulations favor an explanation of the detected excess noise by the presence of multiple charge fluctuators over a single two-level system due to the absence of a bimodal signature in Fig.…”
Section: Resultssupporting
confidence: 76%
“…(ii) The estimated best-fit Δ P ± parameters correlate well with the standard deviation of the P ± in the underlying simulation. (iii) Even a single fluctuator with a fixed switching rate (bimodal distribution of P ± and a Poisson distribution of switching times 40 ) can generate detectable excess noise still consistent with our Dirichlet-based statistical models. As for the physics of the real device in a noisy environment, the simulations favor an explanation of the detected excess noise by the presence of multiple charge fluctuators over a single two-level system due to the absence of a bimodal signature in Fig.…”
Section: Resultssupporting
confidence: 76%
“…In a recent article some of us considered the distribution of waiting times between emitted electrons, and we showed that it contains a wealth of information about the Cooper pair splitter, for instance the characteristic timescales that govern the underlying tunneling processes [51]. Measurements of electron waiting times, however, require real-time detection of the individual tunneling events [52][53][54]. By contrast, conventional quantum transport experiments typically measure the electric currents and their fluctuations [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], which are thus our main focus here.…”
Section: Introductionmentioning
confidence: 99%
“…47 Measurements of electron waiting times, however, require real-time detection of the individual tunneling events. [48][49][50] By contrast, conventional quantum transport experiments typically measure the electric currents and their fluctuations, [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] which are thus our main focus here. In particular, we consider the noise power spectra of the currents in the output leads [51][52][53][54][55] and their power-power correlations, which we use to analyze the physical processes involved in the splitting of Cooper pairs.…”
Section: Introductionmentioning
confidence: 99%